The Bar Butch in the Attic: Lesbian Hauntings in Jane Rule’s “In the Attic of the House” - Wood, Emma (Atlantis, 2024)
In an analysis of Jane Rule’s “In the Attic of the House” from her 1981 anthology Outlander, this article examines how Rule uses both the figure of the lesbian and the figure of the ghost to demonstrate the complex, temporal relationship between two lesbian generations in Canada in the late 1970s and the early 1980s. Rule’s “In the Attic of the House” follows an older butch lesbian, Alice, as she is haunted by both the unseen apparition of her dead, once closeted, femme lover and by the presence of younger lesbian feminists in the main floor of the house who begin to consume and rewrite Alice’s queer past. In analyzing three types of social hauntings within this short story, this article draws on both Avery Gordon’s theories of hauntology and Heather Love’s queer theory of “feeling backwards” to imagine how lesbian-feminists in 1970s-80s Canada conducted a “backward” haunting of femme-butch lesbian elders, hailing from the culture of the lesbian working-class bar. By drawing parallels between Rule’s short fiction and the real, historical events of lesbian communities in Canada, this article seeks to recenter the erasures (i.e., the ghostings) and the (in)visbilities of lesbian existence and embodiment in Canada. This paper ultimately analyzes how Rule as author calls upon her readers to consider and contemplate the historical tensions and intimacies between butch-femme elders of lesbian bar culture and the emerging lesbian-feminist collectives in the early 1980s.